The girls who disappeared : a novel [large type] - Douglas, Claire (Journalist) (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"In a rural Wiltshire town lies the Devil's Corridor--a haunted road which has witnessed eerie happenings, from unexplained deaths to the sounds of a child crying in the night. In this bucolic stretch of Southwest England famous for its otherworldly sites, nothing is more puzzling than the Olivia Rutherford case. Four girls were driving home. After their car crashed only one--Olivia--was found. What happened to the girls who disappeared? On the twentieth anniversary of the tragedy, journalist Jenna Halliday has arrived in Wiltshire to cover the case. The locals aren't happy with this outsider determined to dig into the past. Least of all Olivia"--